2018
DOI: 10.1097/md.0000000000010296
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular metastasis as the first clinical indication of occult lung adenocarcinoma with multiple metastases

Abstract: Rationale:Although metastases to the oral and maxillofacial region (OMR) are rare, the lung is the most common primary site metastasizing to the OMR.Patient concerns:An 83-year-old woman presented with reports of trismus, occlusal discomfort, swelling, and spontaneous pain in the right buccal region. Despite the absence of abnormal chest imaging findings, immunohistochemical analysis of biopsy specimens of the mandible and the thyroid indicated that the patient had multiple metastases from a lung poorly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
0
14
0
3
Order By: Relevance
“…6 It has also been suggested that the posterior mandible is a common site of metastases due to abrupt angulation of the facial vessels at this site, causing slowing of vascular flow that may promote malignant cell deposition. 2 Regardless of the route of travel to the oral cavity, metastases to this area are rare and represent approximately 1% of all oral malignancies. 7 In an analysis of 673 metastatic tumors to the oral cavity, Hirshberg et al reported that metastases to the oral cavity may occur at any age but are most common during the fifth and sixth decades of life, with the site of the primary tumor differing between sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It has also been suggested that the posterior mandible is a common site of metastases due to abrupt angulation of the facial vessels at this site, causing slowing of vascular flow that may promote malignant cell deposition. 2 Regardless of the route of travel to the oral cavity, metastases to this area are rare and represent approximately 1% of all oral malignancies. 7 In an analysis of 673 metastatic tumors to the oral cavity, Hirshberg et al reported that metastases to the oral cavity may occur at any age but are most common during the fifth and sixth decades of life, with the site of the primary tumor differing between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…1 In approximately 20% of patients, oral metastases are discovered before the detection of the primary tumor. 2 We report a man who presented with vague left mandibular pain and new-onset lip numbness as the first sign of occult lung adenocarcinoma.…”
mentioning
confidence: 95%
“…Qualquer neoplasia maligna pode promover a formação de tumores metastáticos para os tecidos do sistema estomatognático, no entanto, a literatura mostra uma maior ocorrência de TMSE associados a neoplasias primárias localizadas em mama, próstata, pulmão, tireoide e rim, perfazendo cerca de 70% dos casos (WU et al, 2017) As metástases de carcinomas pulmonares são mais frequentemente detectados em estágio metastático IV em localizações extra-gnáticas como o fígado, ossos, glândulas suprarrenais e cérebro, no entanto, sugere-se que as lesões metastáticas para a região de cabeça e pescoço usualmente associam-se a tumores primários localizados nos pulmões, com destaque para o carcinoma de células escamosas, seguido do adenocarcinoma (DJERIC et al, 2015;CHENG et al, 2017;MATSUDA, 2018;RADZI, TAN, 2018). Por outro lado, sugere-se que tumores primários do pulmão, pleura, brônquios, esôfago, cólon, mama e pele geralmente metastatizam para a língua (DANIC, DANIC, MACAN, 2018).…”
Section: Principais Neoplasias Associadas a Tmseunclassified
“…A região posterior da mandíbula é afetada na maioria dos casos, principalmente em pacientes dentados, visto que, a presença de dentes nos ossos maxilares parece ser um determinante importante no local preferencial para a ocorrência de metástase, uma vez que podem existir locais hematopoeticamente ativos que permitiriam a atração de células tumorais metastáticas nessa região (MUTTAGI et al, 2011;DALEY, DARLING, 2011;JHAN et al, 2011;KUMAR, MANJUNATHA, 2013;DANIC, DANIC, MACAN, 2018). Ainda nesse contexto acrescenta-se que o sítio mais comum da região crânio facial é a região de molares e pré-molares inferiores, devido a que a angulação abrupta nesta região, parece causar lentidão da corrente sanguínea, facilitando a deposição das células malignas favorecendo, dessa forma, a instalação e progressão da doença metastática na região posterior mandibular (MATSUDA et al, 2018).…”
Section: Características Clínicas E Imaginológicas Dos Tmseunclassified
See 1 more Smart Citation